SENSITIZING TECHNIQUE TO IMPROVE EFL STUDENTS’ READING COMPREHENSION - Khulaifiyah Khulaifiyah (Lectura : Jurnal Pendidikan, 2014)
This study was intended to develop a learning strategy that could improve their readingcomprehension. The strategy selected was sensitizing technique. It was developed forthe sake of improving the students’ reading comprehension, namely: literalcomprehension, interpretive comprehension and critical comprehension. The study wasClassroom Action Research. The procedure of the research consisted of four majorsteps namely; planning, implementing, observing, and reflecting. It consisted of twocycles. Each of them consisted of three meetings for the teaching learning process andone meeting for quiz. The result of the research showed that sensitizing readingtechnique was effective in increasing the students’ reading comprehensionachievements. This fact was clearly indicated by the increasing of percentages ofachievement through the cycles of action that was 52.7 % (Pre-test), 66.9 % (Cycle 1),and 81.8 % (Cycle 2). The scores had fulfilled the criteria of success in implementingsensitizing-reading technique namely the improvement of students’ readingcomprehension ability.